2017
DOI: 10.1182/blood-2017-02-766121
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging activity for R-CHOP in advanced stage nodular lymphocyte–predominant Hodgkin lymphoma

Abstract: Nodular lymphocyte Hodgkin lymphoma (NLPHL) is a rare disease for which the optimal therapy is unknown. We hypothesized that rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) could decrease rates of relapse and transformation. We retrospectively reviewed patients with NLPHL diagnosed between 1995 and 2015 confirmed by central pathologic review. Fifty-nine had sufficient treatment and follow-up data for analysis. We described progression-free survival (PFS), overall survival (OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 28 publications
4
56
0
4
Order By: Relevance
“…In a retrospective study of newly diagnosed adult patients with LPHL ( n = 6), R‐ABVD was efficacious with an estimated 6‐year EFS and OS of 75% and 100% respectively . Similarly, a retrospective analysis of 27 adult patients with advanced‐stage LPHL demonstrated that R‐CHOP was an effective treatment approach with an overall response rate of 100% and a CR rate of 89% …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a retrospective study of newly diagnosed adult patients with LPHL ( n = 6), R‐ABVD was efficacious with an estimated 6‐year EFS and OS of 75% and 100% respectively . Similarly, a retrospective analysis of 27 adult patients with advanced‐stage LPHL demonstrated that R‐CHOP was an effective treatment approach with an overall response rate of 100% and a CR rate of 89% …”
Section: Discussionmentioning
confidence: 98%
“…The National Comprehensive Care Network (NCCN) guidelines (https://www.nccn.org/professionals/physician_gls/pdf/hodgkins.pdf) suggest CVP, ABVD, or CHOP with or without rituximab as the most common regimens for advanced‐stage LPHL in adults. In adult studies of LPHL, rituximab has been used alone and in combination with other chemotherapy with promising results . Rituximab has been used as a single agent to treat 39 adult patients all of whom achieved a CR or PR after four weekly doses, with durable responses seen in patients treated with maintenance rituximab every 6 months for 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Even for patients without a definitive pathological diagnosis of large cell transformation, the presence of high‐risk variant patterns (C–F), B symptoms, bulky disease and infradiaphragmatic disease (especially splenic involvement) are all indications for more aggressive frontline therapy. For these patients, we typically recommend chemotherapy with R‐CHOP (Fanale et al , ). In contrast, for advanced stage patients who are asymptomatic with low tumour burden and without unfavourable clinical or pathological features, an initial strategy of observation is reasonable and does not compromise OS (Borchmann et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report from MDACC hypothesized that rituximab plus cyclophosphamide, doxorubicin, vincristine and prednisone (R-CHOP) could decrease rates of relapse and transformation (Fanale et al, 2017). This study included 59 patients with NLPHL diagnosed from 1995 to 2015 and confirmed by central pathological review.…”
Section: Summary Of Treatment For Early Stage Diseasementioning
confidence: 99%
“…Relapses in NLPHL have been found amenable to salvage chemotherapy, hence the trend toward decreasing the intensity of frontline therapy to minimize the risk of treatment toxicity and late effects . Rituximab has shown potential benefit in frontline as well as salvage treatment in adult NLPHL, however it is yet to be studied in pediatric NLPHL . Recent guidelines recommend complete resection alone in Stage IA NLPHL, with low dose chemotherapy/low dose radiation only in unresectable early stage disease, or in fully grown adolescent with localized disease .…”
Section: Discussionmentioning
confidence: 99%